Un)consequential Planning practices: the political pitfall of mobility policy-making in Lisbon’s Metropolitan Area - Mourato, J.; Almeida, J.; Carmo, R. M.; Caeiro, T. (Networked Urban Mobilities Conference and Mobile Art Exhibition 2014 – Cosmobilities network, 2014)
Mobility is a core concept on the spatial justice (Harvey, 1973; Fainstein, 2009) and the right to the city (Lefebvre, 1968; UNHABITAT 2010) debates. Mobility or lack thereof has become an important force of stratification (Asher, 2010). This is the essence of multiple studies about the production of mobilities (Sheller and Urry, 2006) and its relation to social inequality (Camarero and Oliva, 2008). In Portugal, mobility is a highly contentious and politically sensitive policy field. Public investment has been largely channeled to the development of the national road and highway network. Public transport investment, mainly underground and overground railway, reinforced the classic center-periphery model in the country’s main metropolitan areas of Lisbon (LMA) and Oporto where half the country’s population inhabits. Consequently, thirty years of intense urban expansion have fuelled a highly car dependent metropolitan mobility pattern. In the LMA mobility policy experiences a decade long political stand-off. Notwithstanding, there is growing consensus on the need for an effective supramunicipal transport authority and strategic plan to overcome network management shortfalls and overall system inefficiency. An institutional and legal framework has even been set up with the creation of the metropolitan transport authorities and a renewed legal status for intermunicipal and metropolitan areas. However, the LMA continues to lack political and representative legitimacy and financial power to effectively engage its policy mandate. In this paper we review the implications of this political pitfall in the light of the recent (post-2007) crisis-led socioeconomic changes in Portugal. Building on the preliminary findings of a 2014 LMA-wide survey we explore the relationship between mobility patterns and socioeconomic inequality. Besides space, so gender, age and socio-economic status are determinant in the unequal (re)production of mobilities. Sociospatial differentiation produces different mobility patterns. Subsequently it also contributes to distinct institutional responses in terms of mobility policy design.